Prospects for nucleic acid-based therapeutics against hepatitis C virus - Lee, Chang Ho (Baishideng Publishing Group Co., Limited, 2013)
In this review, we discuss recent advances in nucleic acid-based therapeutic technologies that target hepatitis C virus (HCV) infection. Because the HCV genome is present exclusively in RNA form during replication, various nucleic acid-based therapeutic approaches targeting the HCV genome, such as ribozymes, aptamers, siRNAs, and antisense oligonucleotides, have been suggested as potential tools against HCV. Nucleic acids are potentially immunogenic and typically require a delivery tool to be utilized as therapeutics. These limitations have hampered the clinical development of nucleic acid-based therapeutics. However, despite these limitations, nucleic acid-based therapeutics has clinical value due to their great specificity, easy and large-scale synthesis with chemical methods, and pharmaceutical flexibility. Moreover, nucleic acid therapeutics are expected to broaden the range of targetable molecules essential for the HCV replication cycle, and therefore they may prove to be more effective than existing therapeutics, such as interferon-α and ribavirin combination therapy. This review focuses on the current status and future prospects of ribozymes, aptamers, siRNAs, and antisense oligonucleotides as therapeutic reagents against HCV.